Preliminary study on diminution level of RNA/DNA ratio in tissue of Labeo rohita by exposure to some endocrine disrupting compounds (EDCs) - Rita Verma; Atul K. Singh; Kamal Jaiswal (Aceh Journal of Animal Science, 2016)
Effects of EDCs particularly on RNA/DNA ratio are yet to be investigated to manage the effluents in natural waters. We investigated exposure effects of endocrine disrupting compounds (EDCs) phthalic acid ester (PAE) and hexachlorocyclohexane (HCH) on the RNA/DNA ratio in tissue of an Indian major carp Labeo rohita. Fish were exposed to pre-determined sublethal concentrations of phthalic acid ester (Di-methyl phthalate (DMP), di-butyl phthalate (DBP), and di-(2- ethylhexyl) phthalate (DEHP) and also HCH for determining the tissue RNA/DNA ratio after 30, 60 and 90 days of exposure in the doses of 0.2 mg L-1, 0.3 mg L-1, and 0.5 mg L-1 respectively. All these tested chemicals significantly (P0.05) inhibited RNA/DNA ratio. The ratio gradually significantly (P0.05) decreased after DEHP where it was 1.9±0.51 F1, 18=15.8 P=0.014 n=19; in case of DBP it was 1.92±0.62 F1, 20=6.5 P=0.012 n=19 and for HCH it was 0.94±0.21 F1, 18=18.08 P=0.0012 n=19 at treatments concentrations of 0.3 mg L-1 and 0.5 mg L-1, compared to control (2.9±0.2) after 90 days. However, there was no statistical significance (P0.05) in RNA/DNA ratio after the DMP (F1, 20=2.4 P=0.15n=21) treatment.